Nick Clegg guest speaker at Lunar Society dinner (Birmingham post (Birmingham, England), 2018)
THE Lunar Society hosted members and guests at the Edgbaston Stadium with The Rt Hon Nick Clegg as guest speaker at its annual dinner. Nick spoke about artificial intelligence and machine learning and the impact on politics and society, and touched on the subject of his new book -How To Stop Brexit and Make Britain Great Again, The Society's chair, The Rt Hon Jacqui Smith, introduced the evening's events and touched on how, if the original Lunar men were around today, their focus would have been on some of the technological preoccupations of today, as well as the economic, ethical, social and political opportunities and challenges of the digital age.